Cat scratch disease in an immunosuppressed patient with systemic lupus erythematosus. (March 2016) - Vargas-Hitos, J A; Sabio, J M; Navarrete-Navarrete, N; Arenas-Miras, M del M; Zamora-Pasadas, M; Jiménez-Alonso, J
Cat scratch disease is an infectious disorder transmitted by cats that typically affects children and young adults. Immunosuppression is a well-known risk factor for the development of severe and atypical forms of the disease; hence it is under-diagnosed in patients with compromised immunity. We are reporting the first case of cat scratch disease, which presented as fever and fatigue, in a patient with systemic lupus erythematosus while receiving immunosuppressant therapy after a kidney transplant.